Zooarchaeological analysis of the faunal remains from the Palaeolithic site of La Adam Cave (Dobrogea, SE Romania) – new data from recent excavations - Vasile, Ș.; Dumitrașcu, V. (Materiale și Cercetări Arheologice, 2021)
Recent (2006– 2009) excavations at the Palaeolithic site from La Adam Cave (central Dobrogea, south-eastern Romania) yielded numerous fossil remains, that were analysed in order to obtain more information on the Late Pleistocene faunal assemblage from the area of the cave, on the animal and anthropic contributions to bone accumulation in the cave, and on the taphonomic processes present at the site. The faunal remains analysed were highly fragmented, which prevented the precise taxonomic assessment for most of them. However, numerous specimens bear signs of chemical corrosion and carnivore bite marks, only a few showing signs of anthropic activity. The cave seems to have functioned as shelter for the carnivores, with cave bear remains dominating numerically. Other large carnivores, such as cave hyenas, most probably also contributed to bone accumulation, with large and middle-sized ruminants being their most common prey